Fonctions, utilisations et représentations de l'espace dans les sépultures monumentales du Néolithique européen - Robin, Guillaume; D'Anna, André; Schmitt, Aurore; Bailly, Maxence (Préhistoires de la Méditerranée, 2016)
From Newgrange in Ireland to Hal Saflieni in Malta or Gavrinis in Brittany, Neolithic tombs are well known for their monumental nature. Far from being simple mortuary "containers", only aimed at receiving dead bodies, these tombs are complex and multiple architectures that were designed to host elaborate burial rituals involving several actors and several ceremonial times and spaces. For archaeologists, the spatial organisation of these architectures and their contents is a thread to investigate and understand the burial practices and beliefs of Neolithic communities. Combining recent fieldworks and regional surveys, it explores the configuration of tombs architecture (megalithic chambered tombs, rock-cut tombs, cists under tumulus or cairns, barrows, etc.), the spatial organisation of bodies, grave goods and imagery, and the relationships between the tombs and their landscape setting. This European overview shows the different ways Neolithic societies thought, built and used the space of the dead in Europe from 5000 to 2000 BC. But it also offers and discusses ideas about the meaning of these spatial choices.